ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI KEBIJAKAN UTANG PERUSAHAAN NON KEUANGAN - Purnianti, Ni Komang Ayu; Putra, I Wayan (E-Jurnal Akuntansi; Vol 14 No 1 (2016), 2016)
Debt is one of the sources of external financing used by companies to finance the funding needs of the corporate. The aims of this study is to analyze the impact of the intitutional ownership, managerial ownership, size and age on debt. This research carried out on non-financial companies listed on the Stock Exchange for the 2011-2013. Research using purposive sampling method for taking samplel, and obtained 378 observations. Analysis technique used is multiple regression analysis. The result of research show institutional ownership has negative influence toward debt policy. Managerial ownership have no influence toward debt policy. Size  have positif influence toward debt policy. Age  have negative influence toward debt policy.
Keywords: institutional, managerial, size, age, debt